EFEKTIVITAS PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PERPINDAHAN KALOR - Nuzula Aulia Falihah Rasyidah; Laily Rosdiana (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This research aimed to describe the implementation of learning and students’ learning outcomes on heat transfer material with cooperative learning using audio visual. This research design used one-group pretest-posttest. This research involved 66 students’ in one of public Junior High School in Sidoarjo with 33 students’ of experimental class and 33 students’ of control class. This research's data collection methods included observation, tests, and questionnaires. The results showed that the implementation from two meetings in the experimental class and control class was done with a very good category. Overall, there is an increased of students learning outcomes in experimental class higher than control class. The students' responses from experimental and control class got very good and a quite good category. Therefore, it can be concluded that learning with audio visual is more effective for improve students’ learning outcomes on heat transfer material.